The N-Linked Glycosylation Site N201 in eel Lutropin/Choriogonadotropin Receptor Is Uniquely Indispensable for cAMP Responsiveness and Receptor Surface Loss, but Not pERK1/2 Activity - Munkhzaya Byambaragchaa; Dong-Wan Kim; Sei Hyen Park; Myung-Hwa Kang; Kwan-Sik Min (Current Issues in Molecular Biology)
The seven transmembrane-spanning lutropin/chorionic gonadotropin receptors (LH/CGRs) trigger extracellular signal-related kinases (ERK1/2) via a noticeable network dependent on either G protein (Gαs) or β-arrestins. LH/CGRs are highly conserved, with the largest region within the transmembrane helices and common N-glycosylation sites in the extracellular domain. We aimed to determine the glycosylation sites that play crucial roles in cAMP and pERK1/2 regulation by constructing four mutants (N49Q, N201Q, N306Q, and N312Q). The cAMP response in cells expressing the N201Q mutant was completely impaired, despite high-dose agonist treatment. The cell-surface expression level was lowest in transiently transfected cells, but normal surface loss of the receptor occurred in cells expressing the wild-type and other mutant proteins. However, the N201Q mutant was only slightly reduced after 5 min of agonist stimulation. All mutants showed a peak in cAMP signaling 5 min after stimulation with a pERK1/2 agonist. Of note, cAMP activity was completely impaired in the N201Q mutant; however, this mutant still displayed a pERK1/2 response. These data show that the specific N-linked glycosylation site in eel LH/CGR is clearly distinguished by its differential responsiveness to cAMP signaling and pERK1/2 activity. Thus, we suggest that the cAMP and pERK1/2 signaling pathways involving eel LH/CGRs represent pleiotropic signal transduction induced by agonist treatment.